Young Children’s Indiscriminate Helping Behavior Toward a Humanoid Robot - Martin, Dorothea U.; MacIntyre, Madeline I.; Perry, Conrad; Clift, Georgia; Pedell, Sonja; Kaufman, Jordy (Frontiers in Psychology, 2020)
Young children help others in a range of situations, relatively indiscriminate of the characteristics of those they help. Recent results have suggested that young children’s helping behaviour extends even to humanoid robots. However, it has been unclear how characteristics of robots would influence children’s helping behaviour. Considering previous findings suggesting that certain robot features influence adults’ perception of and their behaviour towards robots, the question arises of whether young children’s behaviour and perception would follow the same principles. The current study investigated whether two key characteristics of a humanoid robot (animate autonomy and friendly expressiveness) would affect children’s instrumental helping behaviour and their perception of the robot as an animate being. Eighty-two 3-year-old children participated in one of four experimental conditions manipulating a robot’s ostensible animate autonomy (high/low) and friendly expressiveness (friendly/neutral). Helping was assessed in an out-of-reach task and animacy ratings were assessed in a post-test interview. Results suggested that both children’s helping behaviour, as well as their perception of the robot as animate, were unaffected by the robot’s characteristics. The findings indicate that young children’s helping behaviour extends largely indiscriminately across two important characteristics. These results increase our understanding of the development of children’s altruistic behaviour and animate-inanimate distinctions. Our findings also raise important ethical questions for the field of child-robot interaction.